EVALUATION OF INTENSIFICATION IMPLEMENTATION OF SOLAR ENERGY by CONSTRUCTING COGNITIVE MAPS - Казак, В.; Ковбій, К.; Панченко, Я. (Science-based technologies, 2011)
The opportunities of intensifying the intensification of solar energy by constructing cognitive maps were evaluated in the article. Analyzing received cognitive map, you can draw conclusions concerning the relationship of factors affecting the implementation of the intensification of solar energy in the Odessa region, to predict the effects of changing one or more factors.